No-Par Stock: Its Economic and Legal Aspects - Bonbright, James C. (Quarterly Journal of Economics, 1924)
Significance of par value, 441. — Difficulties arising from its use, 444. — Removal of par value as a solution of the difficulties, 446. — First objection to the use of shares without par: effect on stockholders' liability, 451. — Their liability under present no-par stock laws, 452. — Can effective liability be secured without par value? 460. — Second objection: that no-par shares may be issued at too low prices, 462. — Conclusions, 464.